Bioremediation of heavily hydrocarbon-contaminated drilling wastes by composting - Paladino, Gabriela Lucía (2016)
Oil-based drilling cuttings comprise a large and hazardous waste stream generated by oil and gas wells drilling operations. Oil-based cuttings are muddy materials with high contents of salts and hydrocarbons. Composting strategies have shown to be effective in the biodegradation of petroleum hydrocarbons, and it offers numerous advantages in comparison with other bioremediation methods. In order to assess the effectiveness of drilling cuttings bioremediation by composting with food and garden wastes, an experiment was conducted in 60-L reactors for 151 days. Four treatments were carried out: only oil-based cuttings, two proportions (in a volume basis) of organic wastes to drilling cuttings (33 and 75 %) and only organic wastes (as a traditional composting reference), with pine-tree woodchips as bulking agent. High degradation percentages of total hydrocarbons (≈82 %), n-alkanes (≈96 %) and the 16 USEPA-listed polycyclic aromatic hydrocarbons (≈93 %) were reached in the treatment with 75 % of organic wastes, and applying 33 % of organic wastes was not more effective than not applying organic wastes for the drilling cuttings hydrocarbons biodegradation. Furthermore, in the treatment with 75 % of organic wastes, alkanes half-life and polycyclic aromatic hydrocarbons half-life were about 10 times and four times lower, respectively, than those in the treatment with 33 % of organic wastes. Possibly, lower hydrocarbons and salts initial concentrations (i.e., lower toxicity), higher microbial counts, adequate nutrient proportions and water content supported a high biological activity with a consequent elevated biodegradation rate in the treatment with 75 % of organic wastes.